Notch1 deficiency alters the migratory behavior of developing T cells and calcium signaling in the thymus of medaka. Issue 2 (17th November 2021) - Aghaallaei, Narges; Inoue, Daigo; Hasel de Carvalho, Eva; Dick, Advaita M.; Wittbrodt, Joachim; Leptin, Maria; Bajoghli, Baubak
Abstract: The differentiation of T cells from lymphoid progenitors in the thymus follows sequential developmental stages that constantly require interaction with thymic epithelial cells. Several distinct aspects of early T cell development depend on the activation of Notch receptors on thymocytes, while the selection of thymocytes at later stages are believed to be Notch independent. Using reverse genetic approaches and whole‐thymus live imaging in an in vivo teleost model, the medaka, we report that Notch1 signals is required for proliferation and specification of developing T cells as well as involved in their selection in the thymus. We reveal that Notch1 controls the migratory behavior of thymocytes through controlling the chemokine receptor Ccr9b and thereby influence the T cell receptor (TCR) activation. Hence, we propose that, in lower vertebrates, the function of Notch signaling extends to all stages of T cell development, except when thymocytes undergo TCRβ rearrangement. Abstract : In lower vertebrates, Notch1b controls the migratory behavior of thymocytes through regulating the chemokine receptor Ccr9b and calcium signaling during thymic selection as revealed by reverse genetic approaches and whole‐thymus live imaging.